THE MAPPING AND ANALYSIS OF DIPHTHERIA CASES IN SURABAYA (2017-2018) - Adelita Setiawan; Lucia Yovita Hendrati; Yudied Agung Mirasa (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2021)
Diphtheria is an acute disease that attacks the airways and causes deaths. The risk factors for diphtheria are low Diphtheria-Pertussis-Tetanus (DPT) immunization coverage and an unhealthy home environment. One effort to control diphtheria is by providing information in the form of the patient's location that makes it easier to determine the target group of people intervened. The city of Surabaya experienced an increase of 50 diphtheria cases from 2017 to 2018. This study aimed to map and analyze diphtheria cases based on DPT immunization and healthy homes from 2017 to 2018 in the city of Surabaya. This study was classified descriptive analytic and used an ecological design. This study used the Pearson's correlation coefficient statistical test to analyze secondary data from the Surabaya City’s Health Profile of 2017 to 2018. This study employed the Health Mapper 4.3.0.0 application and SPSS software version 23. The study variables were diphtheria cases, DPT immunization coverage, and the percentage of healthy homes in 2017 and 2018 in Surabaya. The results of the statistical test indicated that there was a moderate relationship between DPT basic immunization coupon with the number of diphtheria cases in 2018 (p = 0.007; OR = 0.471); while the percentage of healthy homes and the number of diphtheria cases in 2018 showed a strong correlation (p = 0.002; OR = 0.544). The city experienced an increase in the number of diphtheria cases from 2017 to 2018, as well as the rise in DPT immunization coverage and the percentage of healthy homes, which tended to be stagnant. DPT immunization coverage and the percentage of healthy homes based on the 2018 data were related to the number of diphtheria cases in Surabaya. Counseling for the people in the city should be conducted to ensure that their children get DPT immunization and maintain environment cleanliness for a healthy home.